MENINGGKATKAN PRESTASI BAHASA INDONESIA DALAM KEMAMPUAAN MEMECAHKAN SUATU MASALAH MELALUI METODE PEMECAHAN MASALAH (PROBLEM SOLVING ) - Sri Rahayu (MEDIA DIDAKTIKA, 2016)
This study was aimed to determine the increase of Indonesian achievement in the ability of solving a problem through the learning method of resolution (problem solving) and the implementation of learning using learning method of resolution (problem solving) to the Indonesian achievement in the ability of solving a problem at the fifth graders of the state elementary school of Mangkujajar, Kembangbahu District, Lamongan in the academic year of 2015/2016. The research used classroom action research method which consisted of several cycles with each cycle there are planning, action, observation, and reflection. The data was all the fifth graders of the state elementary school of Mangkujajar, Kembangbahu District, Lamongan in the academic year of 2015/2016 in the sum of 20 students. The result of this study indicated that there was a significant problem-solving learning method to increase the ability of students responding to a question.